The Influence of Import Tax Knowledge, Government Trust, Purchasing Preferences on Taxpayer Compliance in Paying International Taxes - Valda, Levina Aprilia; Rachman, Helmy Aulia (AKUNSIKA: Jurnal Akuntansi dan Keuangan, 2025)
In general, a country's revenue is determined by international taxpayer compliance. This study aims to examine the effect of knowledge about import taxes, trust in the government, and purchasing preferences on personal taxpayer compliance in paying import taxes on Korean fandom goods. This study uses a quantitative approach with a sample size of 100 K-POP fan respondents in DKI Jakarta who have purchased Korean fandom merchandise. Data were collected using a purposive sampling method. Data analysis includes validity and reliability testing, classical assumption testing, correlation analysis, and multiple linear regression. Data were processed using SPSS software. The results of the study indicate that import tax knowledge, trust in the government, and purchasing preferences have a positive and significant effect on personal taxpayer compliance in paying international taxes. These findings identify the importance for the government to strengthen tax education programs followed by simplifying the import tax payment process and continuing to build public trust in the government. Keywords: Import tax; Tax compliance; Government trust; Purchase preference; K-POP fandom.